KEANEKARAGAMAN JENIS TUMBUHAN YANG BERPOTENSI SEBAGAI TANAMAN HIAS DALAM KAWASAN IUPHHK-HTI PT. BHATARA ALAM LESTARI DI DESA SEKABUK KECAMATAN SADANIANG KABUPATEN MEMPAWAH - Sriastuti, Widia; Herawatiningsih, Ratna; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2018)
The forest provides many useful things for the survival of living creatures, such as medicines, food, building materials and fresh air and water. In the forest there are also woody vines that can reach high to the top of trees and epiphytes that grow on trees, such as ferns and orchids that have the potential to be ornamental plants. The aim of this research is to find out the diversity of plant species that have potential as ornamental plants such as trees (firs), herbs (hulls), lianas (nepenthes), bushes (ficus elastic), shrubs (Cordlyne fruticosa) and succulents (cactus) within the area of IUPHHK-HTI of PT Bhatara Alam Lestari in Mempawah Regency. The reaearch was conducted with a field survey method, with plot laying observation by multiple plots placed by purposive sampling. The results of observations on 101 observation plots were used as a sample of observation in the area of IUPHHK-HTI of PT. Bhatara Alam Lestari in Sekabuk Village of Sadaniang Subdistrict in Mempawah Regency overall found 30 species of plants that have the potential an ornamental plants. Nepenthaceae and Orchidaceae families are most often encountered as ornamental plants.Keywords: Diversity, Ornamental Plants, Nepenthaceae, Orchidaceae